The effect of human settlement on bird communities in lowland riparian areas - Miller, James R., author; Hobbs, N. Thompson, advisor; Wiens, John A., advisor; Armstrong, David M., committee member; Wilson, Kenneth, committee member (Colorado State University. Libraries, 1999)
I studied the ways that lowland riparian habitats and the bird species that use them change along a gradient of human settlement that proceeds from rural to urban areas on four drainages near the Front Range of Colorado. I examined correlations between settlement intensity, characteristics of riparian woodlands, and the structure and composition of bird communities. In addition, I investigated the effect of development on predation risk in riparian areas using natural and artificial nests. The effect of human activity and recreational trails on predation levels was also examined. The results of these studies demonstrate that avian communities in these riparian woodlands are influenced by a combination of local habitat features and by the level of development in the surrounding landscape.
Keywords: ecology; zoology